#Everything Will Be Fine. Duration of Home Confinement and “All-or-Nothing” Cognitive Thinking Style as Predictors of Traumatic Distress in Young University Students on a Digital Platform During the COVID-19 Italian Lockdown - Giusti, Laura; Salza, Anna; Mammarella, Silvia; Bianco, Denise; Ussorio, Donatella; Casacchia, Massimo; Roncone, Rita (Frontiers in Psychiatry, 2020)
On March 10, 2020, Italy announced its lockdown caused by the novel coronavirus (COVID-19) pandemic, and home confinement exposed individuals to a stressful situation of unknown duration. Our study aimed to analyze the emotional and cognitive experiences and the psychopathological symptoms of young Italian university students seeking help from our university student Counselling and Consultation Service during the COVID-19 lockdown. Also, our study aimed to identify the predictors of traumatic psychological distress, investigating variables that could influence the students' well-being, related to their socio-demographic and clinical condition, to the "exposition" to the social distancing, and related to their cognitive thinking style. One-hundred and three university students were included in our study. The traumatic impact was assessed by the Impact of Event Scale-Revised (IES-R). A digital platform was used in our study, focused on narrative dimensions analyses. Our results showed that 21.4% of our help-seeking students experienced lockdown as a traumatic experience. The main stressful factors reported by students were: adjustment to the new academic activities (23.3 %), lack of autonomy (19.4%), and conflicts with family members (6.8%). The three main areas impaired were: changes in the sleeping pattern (68%), difficulty in concentration (67%), and loss of energy (58.6%). Furthermore, 36% of our student sample reported being suffering from anxiety symptoms, whereas 26% showed depressive symptomatology. Students having previous psychological and psychiatric contacts with mental health services (23%) showed a more severe traumatic and depressive symptomatology. The problematic thinking style "all or nothing" was predominantly associated with psychological distress, anxiety, depression, and posttraumatic symptoms. "Everything Will Be Fine" could be identified by the "optimistic style" (27.2%), inversely correlated with the psychopathological measures and concentration problems. The results of the logistic regression analysis indicated that the length of home confinement (second month) seemed to increase by over 3 times the likelihood of experience posttraumatic symptomatology, and a thinking style "all or nothing" was the final strongest predictor increasing the risk by over 5 times. The implementation of psychological interventions to improve the mental health of vulnerable young subgroups to contain the structuring of psychopathological profiles represent a fundamental challenge.